2006
DOI: 10.1002/ajmg.a.31470
|View full text |Cite
|
Sign up to set email alerts
|

Associated malformations in congenital diaphragmatic hernia cases in the last 15 years in a tertiary referral institute

Abstract: This is a review of cases of perinatally diagnosed congenital diaphragmatic hernia (CDH) with associated malformations with regard to time of diagnosis, side of hernia, associated malformations, and outcome. The authors analyzed the data of CDH cases with associated malformations from records of the I. Department of Obstetrics and Gynecology, Semmelweis University Faculty of Medicine, Budapest, between July 1, 1990 and June 30, 2005. The observed period was analyzed in two parts. The pre- and postnatal examina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 30 publications
1
21
0
Order By: Relevance
“…Associated cardiac anomalies are present in 8% to 51% of all CDHs, whereas noncardiac anomalies are reported in 24% to 48% of cases [3,17,[29][30][31][32]. Consistent with previous studies, our data did not detect any differences in the incidence of cardiac or noncardiac anomalies between R-CDH and L-CDH.…”
Section: Discussionsupporting
confidence: 91%
“…Associated cardiac anomalies are present in 8% to 51% of all CDHs, whereas noncardiac anomalies are reported in 24% to 48% of cases [3,17,[29][30][31][32]. Consistent with previous studies, our data did not detect any differences in the incidence of cardiac or noncardiac anomalies between R-CDH and L-CDH.…”
Section: Discussionsupporting
confidence: 91%
“…Muscle or/and skeletal defects tend to coincide with trisomy [Bollmann et al, 1995;Keeling et al, 1997;Robert et al, 1997b] and several other congenital defects [Mastroiacovo et al, 1992;Bollmann et al, 1995;Tárnok and Méhes, 2002;Harmath et al, 2006;Man and Chang, 2006].…”
Section: Introductionmentioning
confidence: 99%
“…The etiology of musculoskeletal defects is largely unknown [Hösgor and Tibboel, 2004;Anthony et al, 2005;Yang et al, 2006], but an increased risk of one or more of these defects has been reported in association with both low and high maternal age [Mastroiacovo et al, 1992;Bellovits, 2003;Reefhuis and Honein, 2004;Yang et al, 2006], pregestational diabetes [Janssen et al, 1996], nulliparity [Yang et al, 2006], tobacco smoking [Källén, 1997;Man and Chang, 2006], medication use [Giles and Bannigan, 2006;Man and Chang, 2006], fetal alcohol syndrome [Hannigan and Armant, 2000], and iatrogenic reproductive technologies [Farhi and Fisch, 2007]. Muscle or/and skeletal defects tend to coincide with trisomy [Bollmann et al, 1995;Keeling et al, 1997;Robert et al, 1997b] and several other congenital defects [Mastroiacovo et al, 1992;Bollmann et al, 1995;Tárnok and Méhes, 2002;Harmath et al, 2006;Man and Chang, 2006].…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Although the pulmonary hypoplasia associated with CDH most likely is multifactorial and can be heterogeneous among patients, 12,13 it is generally accepted that earlier diagnosis and more-severe compressive herniation are associated with poorer outcomes. 8,14,15 Because pulmonary hypertension is a significant barrier to survival, it is important to note that pulmonary vascular abnormalities worsen with gestational age in CDH-affected fetuses. A morphologic study conducted with human fetuses with CDHs (gestational age: 22-40 weeks) found that, compared with a control group of fetuses whose deaths were attributable to nonpulmonary causes, fetuses with CDHs (especially fetuses at Ͼ34 weeks of gestation) had reduced lung weight and alveolar count and greater arterial wall thickness of distal pulmonary vessels.…”
mentioning
confidence: 99%